Sleep quality among final year students of health sciences at Universiti Sains Malaysia (USM) - Azmi, Noor Farhani Mohamad (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2016)
Sleep has been found to be of the least priority of most individuals especially students; this includes final year students of health sciences. The purpose of this cross sectional was to determine the sleep quality among final year students of health sciences at School of Health Science, USM. Health Believe Model was used as theoretical framework in this study. The objective of this study was to determine the association between age, gender, health science program and academic performance with sleep quality. A set of questionnaire, Pittsburgh Sleep Quality Index (PSQJ) by Buysee ( 1988) was used and 155 final years of health science students in School of Health Sciences, USM were recruited. A pilot study among 30 students were done to check reliabil ity and validity of the questionnaire with the value was 0. 72. Data was analyzed using the software package SPSS version 22. Statistical significance was considered at p value <0.05. During the analysis, the score of sleep quality was evaluated. Among 155 respondents (n=155), 107 (69.0%) respondents showed that they had poor sleep quality and 48 (31 .0%) showed good sleep quality. Using Chi Square test, there was no association between age and gender with sleep quality (p= 0.175) (p=0.835). However there was an association between different programs in health science with sleep quality (p=0.024). Using one way anova test, there is no association between academic performance and sleep quality (p=0.396). The study findings indicated that majority of the final year students of health sciences at School of Health Science, USM have poor sleep quality